2018
DOI: 10.1088/1361-6560/aaebba
|View full text |Cite
|
Sign up to set email alerts
|

A statistically optimized regional thresholding method (SORT) for bone lesion detection in 18F-NaF PET/CT imaging

Abstract: Identification of individual lesions on 18 F-NaF PET bone scans is a time-consuming and often subjective process that makes accurate characterization of disease burden challenging. Current automated methods either underestimate disease or struggle with high false positive rates. We developed a statistically optimized regional thresholding (SORT) method that optimizes detection of bone lesions.This study assessed 18 F-NaF PET/CT scans of 37 bone metastatic prostate cancer patients. Each PET image was divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…( 98 ) conducted a similar analysis on 18 F-NaF PET/CT images in a cohort of 37 mCRPC subjects. Bone lesions were delineated by an automated algorithm that determines the lesion boundaries based on statistically optimised regional thresholding (SORT) which uses a different threshold based on the location of the lesion in the patients skeleton ( 123 ), which were subsequently assigned a classification label by a nuclear medicine physician between 0 and 5 depending on the likelihood of malignancy (0; background ROI, 1; Definite Benign, 5; Definite Malignant). Radiomics features were extracted from both the PET and CT images and used as the input for ML analysis with nine separate learning methods, where the random forest model performed the best under 10-fold cross-validation conditions at discriminating between the 0 + 1 vs. 5 class labels (AUC = 0.95, 95% CI 0.93 – 0.96).…”
Section: Radiomics In Mpca – Resultsmentioning
confidence: 99%
“…( 98 ) conducted a similar analysis on 18 F-NaF PET/CT images in a cohort of 37 mCRPC subjects. Bone lesions were delineated by an automated algorithm that determines the lesion boundaries based on statistically optimised regional thresholding (SORT) which uses a different threshold based on the location of the lesion in the patients skeleton ( 123 ), which were subsequently assigned a classification label by a nuclear medicine physician between 0 and 5 depending on the likelihood of malignancy (0; background ROI, 1; Definite Benign, 5; Definite Malignant). Radiomics features were extracted from both the PET and CT images and used as the input for ML analysis with nine separate learning methods, where the random forest model performed the best under 10-fold cross-validation conditions at discriminating between the 0 + 1 vs. 5 class labels (AUC = 0.95, 95% CI 0.93 – 0.96).…”
Section: Radiomics In Mpca – Resultsmentioning
confidence: 99%
“…9 However, a wide range of cut-off values for this purpose is present in the literature: ADC values from approximately 700-1300 mm 2 /s x 10 −6 10-17 and %SUV max values from 20-50%, 18,19,25,26,29 have been variably suggested. Similarly to the issue of optimising image scaling for manual delineations, experimental factors such as acquisition parameters -b-values in the case of DWI, and other reconstruction factors in PET 30 -significantly impact the accuracy of derived thresholds. Specific to 68 Ga-PSMA, intravesicular accumulation of radioligand may obscure lesions at the prostate base and complicate approaches based on %SUV max .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, future research on a larger cohort should consider whether certain tumour or imaging characteristics in high-intermediate and high risk patients are correlated with discreetly varying optimal window levels as we still observe variations in accuracy in our cohort using the trained window levels. Furthermore, special attention should be paid to the method of image acquisition as it has been demonstrated that several reconstruction parameters may impact the choice of an optimal threshold for threshold-based contouring and window level setting [19].…”
Section: Discussionmentioning
confidence: 99%